Web-Based Futsal Field Rental Information System Using Laravel Framework - Nurdiansyah Ardin; Yulianto Yulianto; Emil Riza Putra (TEPIAN, 2020)
This research is motivated by Vivo Vive Futsal, which schedules and orders the futsal field offline (having to come directly to the futsal field), this is still less effective and efficient. The purpose of this research is to create a web-based futsal field rental information system in vivo vive futsal. The results of this research are that this information system can solve problems such as providing the scheduling process and online futsal field rental without having to come directly to the futsal field.